2007
DOI: 10.4314/bcse.v21i1.61393
|View full text |Cite
|
Sign up to set email alerts
|

<b>Microwave assisted spectrophotometric method for the determination of copper using leucocrystal violet</b>

Abstract: ABSTRACT.A sensitive spectrophotometric method has been developed for the trace determination of copper using leucocrystal violet as chromogenic reagent. The proposed method is based on the reaction of copper(II) with potassium iodide in acid medium to liberate iodine, which oxidizes leucocrystal violet to crystal violet dye having absorption maximum at 590 nm. The reaction between copper and potassium iodide is accelerated by irradiating the mixture with microwave energy for 15 s at 480 W. Beer's law is obeye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In all forthcoming text we use the designation 2MASS J22472238+5801214 or NGC 7380(4) equivalently. The object's classification as HAeBe was discussed by Mathew et al(2010) based on the following characteristics. The object showed near-IR excess of ∼1 mag in extinction corrected (J − H) versus (H − K) color-color diagram.…”
Section: Introductionmentioning
confidence: 99%
“…In all forthcoming text we use the designation 2MASS J22472238+5801214 or NGC 7380(4) equivalently. The object's classification as HAeBe was discussed by Mathew et al(2010) based on the following characteristics. The object showed near-IR excess of ∼1 mag in extinction corrected (J − H) versus (H − K) color-color diagram.…”
Section: Introductionmentioning
confidence: 99%
“…Since the relative shift is 10Å ± 2Å between two nights observations, the emission line is unlikely related to the accretion disk. It is reported that N II λ5530 and λ5535 emission lines have been detected for Ae/Be stars (Mathew & Bhavya 2010;Mathew & Subramaniam 2011). However, no other features are found to support the existence of an Ae/Be star, such as Fe II or O I emission lines.…”
Section: Discussionmentioning
confidence: 98%
“…Up to now, LCV has been used only as a reagent for determination of hydrogen peroxide in water [29], marine water [30], food and rainwater [31], antimony in various environmental and biological samples [32], nitrite in water and soil [33], cypermethrin insecticide in environmental and biological samples [34], copper in environmental samples like tap water, agricultural run plant materials [35], and pharmaceutical samples [35][36][37], detecting trace of blood and as an enhance ment reagent for footwear, tyre and fingerprint impression [38][39][40][41].…”
Section: Hs S Onamentioning
confidence: 99%